Redefinisi Arti Sahabat Dalam Perspektif Kitab Ayub - Gregorius Tri Wardoyo (Sekolah Tinggi Widya Sasana, 2020)
The Book of Job is always related to the question why pious people endure misery. This writing tries to dig the other message of the Book of Job that is friendship. Thence, the question that would be answered in this writing is what the meaning of friends according to the Book of Job. Through narrative analyses, this writing tries to present Job’s friends which construct the whole story in the Book through their dialogs. Starting from the recognition of Satan in the Book of Job as “enemy” or “the accuser”, this writing comes to a conclusion that eventually Job’s wife and friends take the function and roles of Satan as Job’s enemy.